2021
DOI: 10.1371/journal.pone.0244970
|View full text |Cite
|
Sign up to set email alerts
|

Predictive equations for resting metabolic rate are not appropriate to use in Brazilian male adolescent football athletes

Abstract: High accuracy in estimating energy expenditure is essential for enhancing sports performance. The resting metabolic rate (RMR), as a primary component of total energy expenditure (TEE), is commonly estimated using predictive equations. However, these references may not be applicable to adolescent athletes. The purpose of this cross-sectional study was to analyse the differences between predicted RMR in relation to energy expenditure measured by indirect calorimetry (IC) among 45 Brazilian male adolescent footb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, few studies have investigated RMR among adolescent athletes, and only among male soccer players [43][44][45]. In these studies, RMR ratio seems to fluctuate between 0.84 and a maximum of 1.33 [44,45], which is similar to our findings. One of the key mechanisms influencing RMR is FFM, as this is one of the largest determinants, accounting for up to 70% of individual variations and considered the largest component of total energy expenditure [46].…”
Section: Resting Metabolic Ratesupporting
confidence: 89%
See 1 more Smart Citation
“…To the best of our knowledge, few studies have investigated RMR among adolescent athletes, and only among male soccer players [43][44][45]. In these studies, RMR ratio seems to fluctuate between 0.84 and a maximum of 1.33 [44,45], which is similar to our findings. One of the key mechanisms influencing RMR is FFM, as this is one of the largest determinants, accounting for up to 70% of individual variations and considered the largest component of total energy expenditure [46].…”
Section: Resting Metabolic Ratesupporting
confidence: 89%
“…Equations used to calculate predicted RMR are derived from an adult population [41], and the current cut-off value established for low RMR ratio (<0.90) was originally established in adult women [42]. To the best of our knowledge, few studies have investigated RMR among adolescent athletes, and only among male soccer players [43][44][45]. In these studies, RMR ratio seems to fluctuate between 0.84 and a maximum of 1.33 [44,45], which is similar to our findings.…”
Section: Resting Metabolic Ratementioning
confidence: 99%
“…Further research is warranted into the agreeability of the Freire equation in other athletic populations, primarily across high‐level collegiate athletes from a variety of sports (Freire et al, 2021). Other research in men athletes have reported the Harris Benedict equation to be the most accurate prediction equation (Balci et al, 2021; Jagim et al, 2018; Oliveira et al, 2021), which is interesting as it was developed in less active individuals and also does not account for FFM.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the equation of Tinsley et al was developed in muscular men and women physique athletes, and is also largely based on FFM (Tinsley et al, 2018). Among the sample initially Other research in men athletes have reported the Harris Benedict equation to be the most accurate prediction equation (Balci et al, 2021;Jagim et al, 2018;Oliveira et al, 2021), which is interesting as it was developed in less active individuals and also does not account for FFM. For women, the De Lorenzo equation demonstrated the strongest agreeability with measured RMR values, which is in agreement with prior in athletic populations (Frings-Meuthen et al, 2021;Haaf & Weijs, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high cost and necessity of trained professionals, IC is the best method for evaluating RMR. Predictive equations would be an alternative for estimating RMR, but unfortunately, most perform poorly in adolescent non-athletes [ 30 , 31 ] and adolescent athletes [ 5 , 32 ]. IC assessments in athletes are relatively complex because of the duration of the current protocols (~60 min if the acclimation period prior to the RMR assessment is considered) and their training and competition schedules [ 27 , 33 ].…”
Section: Discussionmentioning
confidence: 99%